Comparative analysis of the use of space in 7-a-side and 8-a-side soccer: how to determine minimum sample size in observational methodology - Daniel Lapresa; Ildefonso Álvarez; M. Teresa Anguera; Javier Arana; Belén Garzón (Desafio Singular, 2016)
In 2011-2012, the Spanish Soccer Federation changed the format of junior championship matches played between regional-level teams in Spain from a 7-a-side to an 8-a-side format. Soon afterwards, the regional federations followed in their footsteps by adapting their competition formats accordingly. Taking the use of space as a functional indicator of the quality of play in U-10 soccer, the present study examines the relative suitability of the 7-a-side and 8-a-side formats for developing the skills of young players. Of 9 hypothesis contrasts relating to the zone in which a move initiated in the attacking team's goal area ended, only one was significant (p < .05) in the standard analysis, even though the contingency tables suggested there were genuine differences between the two formats studied. Consequently, the statistical software program GPower was used to determine the minimum sample size necessary to detect significant differences for four levels of statistical power: 95%, 90%, 85%, and 80%. Given the difficulty of organizing a new round of data collection, we simulated an increase in sample size while maintaining the characteristics of the original data (frequencies, variability, and distribution). The results obtained through the original sampling were then compared with those from the simulation.